2021
DOI: 10.5194/bg-18-6077-2021
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling spatial and temporal heterogeneity of a tropical forest canopy using high-resolution NIRv, FCVI, and NIRvrad from UAS observations

Abstract: Abstract. Recently, remotely sensed measurements of the near-infrared reflectance (NIRv) of vegetation, the fluorescence correction vegetation index (FCVI), and radiance (NIRvrad) of vegetation have emerged as indicators of vegetation structure and function with potential to enhance or improve upon commonly used indicators, such as the normalized difference vegetation index (NDVI) and the enhanced vegetation index (EVI). The applicability of these remotely sensed indices to tropical forests, key ecosystems for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Based on the idea that the near‐infrared radiation reflected by plants is proportional to the PAR absorbed by plants, the near‐infrared reflectance of vegetation (NIR v ) has shown strong linear relationships with GPP and can be correlated with fAPAR (Badgley et al., 2017, 2019; Baldocchi et al., 2020; Wu et al., 2020). Furthermore, a radiance based (NIR v ) was also correlated with GPP and APAR across agricultural sites and tropical forest canopies (Merrick et al., 2021; Wu et al., 2020). On the ground, temperature‐respiration relationships and light response curves calculated from solar radiation incident on the surface are widely used to partition Net Ecosystem Exchange (NEE) from eddy covariance towers into GPP and ecosystem respiration (R eco ; Lasslop et al., 2010; Reichstein et al., 2012; Stoy et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the idea that the near‐infrared radiation reflected by plants is proportional to the PAR absorbed by plants, the near‐infrared reflectance of vegetation (NIR v ) has shown strong linear relationships with GPP and can be correlated with fAPAR (Badgley et al., 2017, 2019; Baldocchi et al., 2020; Wu et al., 2020). Furthermore, a radiance based (NIR v ) was also correlated with GPP and APAR across agricultural sites and tropical forest canopies (Merrick et al., 2021; Wu et al., 2020). On the ground, temperature‐respiration relationships and light response curves calculated from solar radiation incident on the surface are widely used to partition Net Ecosystem Exchange (NEE) from eddy covariance towers into GPP and ecosystem respiration (R eco ; Lasslop et al., 2010; Reichstein et al., 2012; Stoy et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The three vegetation indices (NDVI, EVI, and NIRv) showed comparable performance for estimating GPP. In the following analyses, we only provide the results from NDVI because it is a simple and most widely used vegetation index, and previous studies also showed its smaller diurnal variations and lower sensitivity to BRDF effects compared to EVI or NIRv ( 64 , 65 ).…”
Section: Methodsmentioning
confidence: 99%
“…NDVI, Normalized Differential Vegetation Index; VOD, vegetation optical depth; UAS, unmanned aerial system. and near-infrared (c. 830-850 nm) data that can be converted to standard satellite-based resilience metrics such as NDVI (Merrick et al, 2021;Figure 5). Hyperspectral imagery on UASs can also be integrated with optical imagery and used to detect tree species (Nevalainen et al, 2017).…”
Section: F I G U R Ementioning
confidence: 99%